2012
DOI: 10.1111/j.1440-1746.2012.07270.x
|View full text |Cite
|
Sign up to set email alerts
|

YKL‐40‐gene polymorphism affects acute cellular rejection and fibrosis progression after transplantation for hepatitis C virus‐induced liver disease

Abstract: Fibrosis progression and ACR-incidence after transplantation for HCV-induced liver disease seem to be under genetic control. The negative impact of G-allele on post-transplant events observed in our study, deserves attention and should be verified in larger liver transplantation-cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…A number of abstracts focused on polymorphisms, immunosuppressive therapy, and donor factors associated with HCV recurrence and antiviral responses. YKL‐40 gene polymorphisms (G allele) were highly associated with both rejection and HCV fibrosis and portended a poor outcome 3. Data on IL‐28B polymorphisms showed a high correlation with the TT genotype and the risk of post‐LT diabetes4 and supported the known association with this genotype and the lack of an antiviral response 1.…”
Section: Viral Hepatitismentioning
confidence: 71%
“…A number of abstracts focused on polymorphisms, immunosuppressive therapy, and donor factors associated with HCV recurrence and antiviral responses. YKL‐40 gene polymorphisms (G allele) were highly associated with both rejection and HCV fibrosis and portended a poor outcome 3. Data on IL‐28B polymorphisms showed a high correlation with the TT genotype and the risk of post‐LT diabetes4 and supported the known association with this genotype and the lack of an antiviral response 1.…”
Section: Viral Hepatitismentioning
confidence: 71%
“…Additionally, YKL-40-gene polymorphism involves in acute cellular rejection and fibrosis progression after liver transplantation with HCV infection. A nucleotide substitution in YKL-40-gene (rs4950928; chromosome 1; G->C) induced higher YKL-40-levels in serum and more severe fibrosis in the presence of C-allele in HCV infection (23,24). A previous study reported that HCV modulates YKL-40 through the NOTCH signaling pathway (25).…”
Section: Introductionmentioning
confidence: 97%
“…These clinical risk factors can only in part explain why some patients develop very fast RC, within a few years after LT, while others show no significant fibrosis at the 5-year protocol biopsy [12]. Beside factors related to the ORIGINAL PAPER transplant procedure or the immunosuppressive management, genetic factors of the donor or recipient appear to influence FP after LT [13].…”
Section: Introductionmentioning
confidence: 99%